Pengaruh Kemudahan Penggunaan dan Kegunaan Terhadap Keputusan Penggunaan E-wallet di Kalangan Mahasiswa Fakultas Ekonomi Undiksha - Ketut Putri Hema Malini; M. Rudi Irwansyah (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2025)
This study aims to determine (1) the effect of ease of use, (2) usability, (3) and the decision to use E-wallet. The population in this study, namely students of the Faculty of Economics, Ganesha University of Education class of 2024, totaling 756 people. The sampling technique in this study used the proportional random sampling technique with a sample size of 161 people. The data collection method used a questionnaire and was analyzed using multiple linear regression analysis. Hypothesis testing used the t-test and F-test which were processed with the help of SPSS (Statistical Package for the Social Sciences) version 25. The results of the study showed that (1) ease of use had a negative and significant effect on the decision to use E-wallet, (2) usability had a positive and significant effect on the decision to use E-wallet, and (3) ease of use and usability had a positive and significant effect on the decision to use E-wallet. This study provides practical implications for E-wallet application developers to improve service usability but with attention to interface simplicity. The unique findings regarding the negative effect of ease of use indicate the need for a balance between advanced features and ease of operation. For financial institutions and governments, the results of this study can be a reference in formulating digital financial inclusion policies among the younger generation, especially students.